Les genres récrits n° 5 - Daniel Elmiger (Glad!)
Names, notably first names, are a central part of an identity – yet they are usually chosen by people other than those who bear them. What happens if someone wants to change their first name (and sometimes also their pronoun)? While this choice is possible in some contexts (e.g., at the Université du Québec à Montréal), it often remains a symbolically important act, but without strong legal consequences. Why should the choice of first name/pronoun not be left to the choice of any person, so that these identification marks are in harmony with their identity?